2012
DOI: 10.1080/02640414.2012.712715
|View full text |Cite
|
Sign up to set email alerts
|

The effect of playing tactics and situational variables on achieving score-box possessions in a professional soccer team

Abstract: The aim of this study was to analyse the influence of playing tactics, opponent interaction and situational variables on achieving score-box possessions in professional soccer. The sample was constituted by 908 possessions obtained by a team from the Spanish soccer league in 12 matches played during the 2009-2010 season. Multidimensional qualitative data obtained from 12 ordered categorical variables were used. Sampled matches were registered by the AMISCO PRO system. Data were analysed using chi-square analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
153
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 16 publications
25
153
3
8
Order By: Relevance
“…Although physical performances are not associated with success, they impact technical proficiency (Rampinini et al, 2008), thus they should not be disregarded as contributors to overall performance. However, BP, number of passes and pass completion rates are all associated with team success and thus are important technical variables (Castellano, Casamichana, & Lago, 2012;Collet, 2013;Lago-Ballesteros, Lago-Penas, & Rey, 2012). We expected HPBPT to be technically superior to LPBPT and our data supports this notion as players in HPBPT performed ~45% more passes than LPBPT, in addition to higher pass completion rates (79 vs 73%).…”
Section: Discussionsupporting
confidence: 77%
“…Although physical performances are not associated with success, they impact technical proficiency (Rampinini et al, 2008), thus they should not be disregarded as contributors to overall performance. However, BP, number of passes and pass completion rates are all associated with team success and thus are important technical variables (Castellano, Casamichana, & Lago, 2012;Collet, 2013;Lago-Ballesteros, Lago-Penas, & Rey, 2012). We expected HPBPT to be technically superior to LPBPT and our data supports this notion as players in HPBPT performed ~45% more passes than LPBPT, in addition to higher pass completion rates (79 vs 73%).…”
Section: Discussionsupporting
confidence: 77%
“…Although the physical and tactical aspects are central to performance (Bradley et al, 2013;Lago-Ballesteros et al, 2012), a teams technical ability has been identified as the best indicator of success (Castellano et al, 2012;Collet, 2013;Rampinini, Impellizzeri, Castagna, Coutts, & Wisløff, 2009). The number of passes performed in World Cup final matches has been shown to have increased by ~40% over four decades (Wallace & Norton, 2014), a similar increase to that observed over a seven year period in the EPL (Barnes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although team success is complex and multifactorial, technical indicators have been found to predict team success more accurately than physical indicators (Carling, 2013;Castellano, Casamichana, & Lago, 2012). More specifically, ball possession, number of shots, shots on target, number of passes and pass completion rates are all associated with team success (Castellano et al, 2012;Collet, 2013;Hughes & Franks, 2005;Lago-Ballesteros et al, 2012;Lago-Peñas & Lago-Ballesteros, 2011). Although physical performances are not associated with success, they impact technical proficiency (Rampinini et al, 2008), thus should not be disregarded as contributors to overall performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…higher passes to shots on goal ratio) and the type of offensive strategy (e.g. direct and counterattack) also important factors related to success (Collet, 2012;Lago-Ballesteros, Lago-Penas, & Rey, 2012). Studies on ball possession have primarily focused on its determinants and little attention has been paid to its interaction with physical indicators (Lago, 2009;Lago & Martin, 2007).…”
Section: Introductionmentioning
confidence: 99%